Intralesional immunotherapy for melanoma. Issue 4 (3rd December 2013) - Hersey, Peter; Gallagher, Stuart; Thompson, John F.
<x xml:space="preserve">Abstract</x> Intralesional immunotherapy of melanoma has two complementary aims. One is to cause regression of the injected metastasis. The other is to incite or modulate systemic immune responses in such a way that non‐injected metastases will also undergo regression. A number of phase 1 and phase II studies with cytokines, viral, or bacterial agents have been conducted but their use has remained sporadic and has not progressed to become established treatments. Two treatments have progressed to randomized phase III studies. The most promising of these is based on intralesional injection of a genetically modified herpes simplex virus (HSV) (T‐Vec). Initial results have shown a significant effect on durable response rates (DRR) but effects on overall survival remain under study. The second involved injection of plasmids coding for the HLA B7 antigen (Allovectin). Despite encouraging early results the treatment did not reach its endpoints and its use has been discontinued. A phase II study involving intralesional injection of oncolytic A21 coxsackie virus (Cavatak) is also under way and is showing promise. J. Surg. Oncol. 2014 109:320–326. © 2013 Wiley Periodicals, Inc.